De novo reconstitution of chromatin using wheat germ cell-free protein synthesis. - Endo, Y.; Takemori, N.; Nagy, S.K.; Okimune, K.I.; Kamakaka, R.; Onouchi, H.; Takasuka, T.E. (FEBS open bio, 2021)
DNA is packaged with histones to form chromatin that impinges on all nuclear processes, including transcription, replication and repair, in the eukaryotic nucleus. A complete understanding of these molecular processes requires analysis of chromatin context in vitro. Here, Drosophila four core histones were produced in a native and unmodified form using wheat germ cell-free protein synthesis. In the assembly reaction, four unpurified core histones and three chromatin assembly factors (dNAP-1, dAcf1 and dISWI) were incubated with template DNA. We then assessed stoichiometry with the histones, nucleosome arrays, supercoiling and the ability of the chromatin to serve as a substrate for histone-modifying enzymes. Overall, our method provides a new avenue to produce chromatin that can be useful in a wide range of chromatin research.